2020
DOI: 10.1007/s42399-020-00230-2
|View full text |Cite
|
Sign up to set email alerts
|

Tenodesis Effect Mimicked by Flexor Tendon Entrapment in a Paediatric Midshaft Forearm Fracture: a Case Report and Review of the Literature

Abstract: Entrapment of the flexor digitorum profundus (FDP) tendon following radius and ulna midshaft paediatric forearm fractures has been reported rarely in the literature. To date, 19 cases have been described. A characteristic fracture pattern, persistent cortical defect at the fracture site and flexion contracture not responsive to hand therapy are all hallmarks of the condition. We present a case along with a review of the literature. A 12-year-old boy underwent exploration of a primary right open radius and ulna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The period from injury to FDP release surgery ranged from 2 days to 16 years. 1 A previous study suggested that two mechanisms underlie entrapment. 2 In the first mechanism, the muscle belly becomes directly sandwiched between the fractured areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The period from injury to FDP release surgery ranged from 2 days to 16 years. 1 A previous study suggested that two mechanisms underlie entrapment. 2 In the first mechanism, the muscle belly becomes directly sandwiched between the fractured areas.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one similar cases have been found to date. 1 Surgical treatment was performed in all cases, and the fractured part was deployed openly to prevent the detachment of muscles and tendons. All subjects were aged between 5 and 17 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Review of the literature reveals 31 cases (both children and adults) of FTE after forearm fractures. [2][3][4][5][6][7][8][9]12,13] In 13 of previous 31 cases, only one finger was affected, while two or more fingers were affected in 18 cases. [2][3][4][5][6][7][8][9]12,13] The average age of patients is 11.6 years ranging from 4 to 28.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Nerve and tendon entrapment in the fracture line after reduction are rarely reported complication of these fractures. [3][4][5][6][7][8][9][10][11][12][13] Flexor tendon entrapment (FTE) is a rare and usually lately diagnosed complication of pediatric forearm fractures. In this case report, we present a case of a neglected ring and little finger flexor digitorum profundus (FDP) entrapment after closed reduction of both bone forearm fracture and treated five years later due to late diagnosis.…”
Section: Case Reportmentioning
confidence: 99%